2013
DOI: 10.3747/pdi.2011.00205
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Influences Peritoneal Morphology in Uremic Patients at the Initiation of Peritoneal Dialysis

Abstract: BackgroundThe peritoneum begins to undergo morphologic changes before the start of peritoneal dialysis (PD), particularly in diabetic patients. The present study was conducted to investigate the effects of diabetes on the peritoneum.MethodsThis study involved 17 patients who began receiving PD and had diabetes as an underlying disease (DM group), and 30 patients without diabetes who served as a control group (nonDM group). At the start of PD, the parietal peritoneum was sampled to assess submesothelial connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 31 publications
(41 reference statements)
0
19
0
1
Order By: Relevance
“…In their classic study, Williams et al [29] did not detect differences in the interstitial and vascular changes observed in peritoneal biopsies from diabetic and nondiabetic patients on PD. On the contrary, a more recent study [30] detected an increased thickness of the submesothelial space and a higher capillary density in peritoneal biopsies from diabetics starting PD. These changes could exert an additive effect to impair transperitoneal water transport, with less predictable effects on small solute transport, which essentially agrees with our results.…”
Section: Discussionmentioning
confidence: 88%
“…In their classic study, Williams et al [29] did not detect differences in the interstitial and vascular changes observed in peritoneal biopsies from diabetic and nondiabetic patients on PD. On the contrary, a more recent study [30] detected an increased thickness of the submesothelial space and a higher capillary density in peritoneal biopsies from diabetics starting PD. These changes could exert an additive effect to impair transperitoneal water transport, with less predictable effects on small solute transport, which essentially agrees with our results.…”
Section: Discussionmentioning
confidence: 88%
“…To the best of our knowledge, only a few studies have reported on the methodology of peritoneal biopsy [7][8][9][10]. Moreover, a detailed biopsy procedure has been described in only one study [7], where the authors have proposed a suture method for collecting peritoneal samples.…”
Section: Past Reports and Issues About Peritoneal Biopsymentioning
confidence: 99%
“…The purpose of a peritoneal biopsy is to evaluate the degree of peritoneal damage caused by PD and to evaluate the risk for EPS progression. The evaluation items include denudation of and morphological changes in mesothelial cells [1,8], thickness and degeneration of submesothelial connective tissue [1-3, 8, 12-18], degree of vasculopathy [1-3, 8, 12-20], angiogenesis [1,8,12,[14][15][16][17][20][21][22], and presence of new membrane formation on the existing peritoneum [15,17]. The thickness of the submesothelial connective tissue is usually measured based on the thickness of the so-called submesothelial compact zone (SCZ) immediately below the mesothelial cell layer to the fatty tissue layer.…”
Section: Histological Analysesmentioning
confidence: 99%
See 2 more Smart Citations